CD4+ T Cell Interstitial Migration Controlled by Fibronectin in the Inflamed Skin - Ninoshka R. J. Fernandes; Ninoshka R. J. Fernandes; Nicholas S. Reilly; Dillon C. Schrock; Denise C. Hocking; Denise C. Hocking; Patrick W. Oakes; Patrick W. Oakes; Deborah J. Fowell (Frontiers in Immunology, 2020)
The extracellular matrix (ECM) is extensively remodeled during inflammation providing essential guidance cues for immune cell migration and signals for cell activation and survival. There is increasing interest in the therapeutic targeting of ECM to mitigate chronic inflammatory diseases and enhance access to the tumor microenvironment. T cells utilize the ECM as a scaffold for interstitial migration, dependent on T cell expression of matrix-binding integrins αVβ1/αVβ3 and tissue display of the respective RGD-containing ligands. The specific ECM components that control T cell migration are unclear. Fibronectin (FN), a canonical RGD-containing matrix component, is heavily upregulated in inflamed tissues and in vitro can serve as a substrate for leukocyte migration. However, limited by lack of tools to intravitally visualize and manipulate FN, the specific role of FN in effector T cell migration in vivo is unknown. Here, we utilize fluorescently-tagged FN to probe for FN deposition, and intravital multiphoton microscopy to visualize T cell migration relative to FN in the inflamed ear dermis. Th1 cells were found to migrate along FN fibers, with T cells appearing to actively push or pull against flexible FN fibers. To determine the importance of T cell interactions with FN, we used a specific inhibitor of FN polymerization, pUR4. Intradermal delivery of pUR4 (but not the control peptide) to the inflamed skin resulted in a local reduction in FN deposition. We also saw a striking attenuation of Th1 effector T cell movement at the pUR4 injection site, suggesting FN plays a key role in T cell interstitial migration. In mechanistic studies, pUR4 incubation with FN in vitro resulted in enhanced tethering of T cells to FN matrix, limiting productive migration. In vivo, such tethering led to increased Th1 accumulation in the inflamed dermis. Enhanced Th1 accumulation exacerbated inflammation with increased Th1 activation and IFNγ cytokine production. Thus, our studies highlight the importance of ECM FN fibrils for T cell migration in inflamed tissues and suggest that manipulating local levels of ECM FN may prove beneficial in promoting T cell accumulation in tissues and enhancing local immunity to infection or cancer.